Population genetic structure of the Antarctic ascidian Aplidium falklandicum from Scotia Arc and South Shetland Islands - Demarchi, Maria Milagros; Chiappero, Marina Beatriz; Tatian, Marcos; Sahade, Ricardo Jose (Polar Biology)
In sessile marine organisms, gene flow between populations depends mainly on free-living reproductive stages (such as larvae and gametes), and usually the strength of genetic structure is related to the time spent in the plankton and physical factors as oceanographic conditions. In Antarctica, abyssal depths that surround the continent and the Polar Front are considered strong barriers for benthic marine fauna, keeping the continent isolated from other shelves. The only available shallow water habitats between South America and the Antarctic continent are those around the Scotia Arc Islands; there are no shallow water habitats between the other southern continents and Antarctica. In this work, ISSRs-PCR markers were used to study the genetic structure of populations of Aplidium falklandicum, a compound ascidian with short-lived lecitotrophic larvae. A highly significant genetic differentiation (ΦST = 0.405; P < 0.05) and a pattern of isolation by distance were found. A genetic landscape approach identified a discontinuity in genetic diversity, coincident with the southernmost registered position of the Polar Front. For A. falklandicum, a species with presumably low capacity of long distance dispersal, the abyssal depths together with the large geographic distances create a barrier for gene flow. Fil: Demarchi, Maria Milagros. Universidad Nacional de Córdoba. Facultad de Cs.exactas Fisicas y Naturales. Departamento de Diversidad Biologica y Ecologica. Cat.de Ecologia Marina; Argentina. Universidad Nacional de Córdoba. Facultad de Cs.exactas Físicas y Naturales. Cátedra de Genética de Poblaciones y Evolución; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba; Argentina Fil: Chiappero, Marina Beatriz. Universidad Nacional de Córdoba. Facultad de Cs.exactas Físicas y Naturales. Cátedra de Genética de Poblaciones y Evolución; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - ...